2021
DOI: 10.3389/fonc.2021.700088
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Treatment Strategies on the Long-Term Prognosis of T1 Stage Esophageal Cancer Patients

Abstract: ObjectiveTo compare the long-term prognosis effects of non-esophagectomy and esophagectomy on patients with T1 stage esophageal cancer.MethodsAll esophageal cancer patients in the study were included from the National Surveillance Epidemiology and End Results (SEER) database between 2005-2015. These patients were classified into non-esophagectomy group and esophagectomy group according to therapy methods and were compared in terms of esophagus cancer specific survival (ECSS) and overall survival (OS) rates.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, EMR is the treatment of choice where this a visible neoplasia. This is because there is no significant difference between EMR and ESD in local recurrence rates, positive margins, LNM, complications, or need for surgery despite the limitations of EMR[ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, EMR is the treatment of choice where this a visible neoplasia. This is because there is no significant difference between EMR and ESD in local recurrence rates, positive margins, LNM, complications, or need for surgery despite the limitations of EMR[ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the probability of postoperative complications and mortality, endoscopic therapy has increasingly become an alternative treatment modality for patients with early EC 7 . Some previously published studies have demonstrated that the prognosis of patients with early EC treated with radical surgery or endoscopic resection was equivalent 8–10 ; for the patients with LNM, however, endoscopic resection can lead to disease recurrence and poor prognosis, given that a cure is sometimes not achieved. Endoscopic ultrasound (EUS) is typically performed to assess the T stage of patients with EC, with high accuracy; however, this procedure has limitations in discovering occult nodal metastases 11,12 .…”
Section: Introductionmentioning
confidence: 99%